2018
DOI: 10.1111/jpn.12910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pure plant secondary metabolites on methane production, rumen fermentation and rumen bacteria populations in vitro

Abstract: In this study, the effects of seven pure plant secondary metabolites (PSMs) on rumen fermentation, methane (CH ) production and rumen bacterial community composition were determined. Two in vitro trials were conducted. In trial 1, nine concentrations of 8-hydroxyquinoline, α-terpineol, camphor, bornyl acetate, α-pinene, thymoquinone and thymol were incubated on separate days using in vitro 24-hr batch incubations. All compounds tested demonstrated the ability to alter rumen fermentation parameters and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
4
18
0
3
Order By: Relevance
“…In the present study, thymol at doses of 100 mg/L and 200 mg/L tended to increase butyrate concentration while a dramatical decrease was observed with 400 mg/L of thymol supplementation. The increase in butyrate concentration is consistent with previous study by Joch et al [ 13 ] with 240 mg/L thymol supplemented to dairy cow in vitro. The dramatical decrease in butyrate concentration caused by highest dose implicates a strong inhibitory effect of high dose thymol in the present study, which is in accord with previous results, i.e., total gas production, IVDMD, and total VFA production.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, thymol at doses of 100 mg/L and 200 mg/L tended to increase butyrate concentration while a dramatical decrease was observed with 400 mg/L of thymol supplementation. The increase in butyrate concentration is consistent with previous study by Joch et al [ 13 ] with 240 mg/L thymol supplemented to dairy cow in vitro. The dramatical decrease in butyrate concentration caused by highest dose implicates a strong inhibitory effect of high dose thymol in the present study, which is in accord with previous results, i.e., total gas production, IVDMD, and total VFA production.…”
Section: Discussionsupporting
confidence: 92%
“…Thymol (5-methyl-2-isopropylphenol) is one of the active compounds in EOs derived from Thymus and Origanum plants [ 11 , 12 ]. Dosages of thymol higher than 240 mg/L have been reported to affect rumen fermentation with a decrease in methanogenesis and altered rumen bacteria composition in lactating cows in vitro [ 13 ]. A similar effect on rumen methane reduction was found by Castañeda-Correa et al [ 14 ] with 200 mg/L thymol supplemented in vitro, whereas no effect was found on dry matter digestibility and methanogenic bacteria except for individual bacterial population changes within rumen microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The major fermentation product of this bacterial family is succinate which is subsequently converted to propionate in the rumen, so it creates the possibility of competition between Succinivibrioanceae and methanogens to utilize hydrogen as a substrate to produce succinate and propionate instead of methane. In line with this, greater abundance of Succinivibrioanceae was negatively correlated with methane production (R = −0.72) in cattle (102). Substantially higher abundance of Succinivibrioanceae has been observed in beef cattle with low methane production compared to cattle with higher emissions (103).…”
Section: Rumen Bacterial Diversitysupporting
confidence: 65%
“…Our results are consistent either with the direct effects of the bioactive compounds of Plants on methanogens or the indirect effect on reducing hydrogen production as a substrate for micro‐organisms (Tavendale et al, 2005). Even though the effect of a medicinal plant enriched diet on gastrointestinal fermentation patterns in vitro can usually be within the physiological range, the efficacy of PSM on rumen fermentation, methane production and rumen bacterial communities can vary considerably depending on the type, sources, molecular weight and doses of the diet (Joch, Mrázek, Skřivanová, Čermák, & Marounek, 2018; Patra et al, 2017).…”
Section: Discussionmentioning
confidence: 99%